The Leaving Certificate and first year university performance - Moran, M. A.; Crowley, M. J. (Statistical and Social Inquiry Society of Ireland, 1979)
The manner in which students are admitted for third level education and in particular the points system have become matters of increasing public controversy in recent years. While the subject is understandably emotive, a sad feature of many of the arguments presented to date has been the very limited factual support. Our purpose in this paper is threefold: firstly to introduce some research which has and is being carried out at University College Cork on the effectiveness of performance in the Leaving Certificate examination and in such alternatives as scholastic aptitude and personality tests, as measures of subsequent university performance; secondly, to suggest some statistical methodology for the analysis of data in this area; and thirdly to offer some personal comments on aspects of the overall problem in an effort to establish a fair and hopefully constructive viewpoint and to redress some misconceptions.
Read before the Society, 24 May 1979
Keywords: Second Level education, Ireland; Leaving Certificate; University performance; Third Level education, Ireland; 314.15